2012
DOI: 10.1002/j.0022-0337.2012.76.6.tb05303.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Choice of Dentists: How and Why People Choose Dental School Faculty Members as Their Oral Health Care Providers

Abstract: This study aimed to better understand how and why people choose dental school faculty members as their oral health care providers. Increasing inancial constraints in U.S. dental schools have led their administrators to seek alternative funding sources, one of which can be revenues from dental school faculty practice. To effectively promote faculty practice, it is necessary to understand how and why one chooses a dental school faculty member as his or her oral health care provider. A survey of 1,150 dental scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 7 publications
(14 reference statements)
5
32
3
Order By: Relevance
“…In another study (17) , the dental consumers not only used the web based information sources heavily, but also considered them to be highly important factor affecting their choice. The differences from our study could be attributed to the fact that either design of the home pages of some practices is either not attracting enough or lacks sufficient information and needs revision.…”
Section: Discussionmentioning
confidence: 99%
“…In another study (17) , the dental consumers not only used the web based information sources heavily, but also considered them to be highly important factor affecting their choice. The differences from our study could be attributed to the fact that either design of the home pages of some practices is either not attracting enough or lacks sufficient information and needs revision.…”
Section: Discussionmentioning
confidence: 99%
“…Expertise and experience of providers, information provision, provider atmosphere, and waiting time were identified as important attributes of a health care service . More specifically, a study of Kim et al suggested that the quality of care, professional competence of dentist, explanation of the treatment/patient participation in the treatment decision, ability to get appointments at a convenient time, reasonable waiting time to get appointment, and attitude/helpfulness of staff are the most important factors in the choice of a dentist. Out‐of‐pocket costs were also identified as an important factor .…”
Section: Methodsmentioning
confidence: 99%
“…This extends to choices in healthcare providers. In human healthcare, individuals use websites to select dentists (Kim et al 2012), and in some countries, hospitals (Norum and Moen 2004;Leister and Stausberg 2007).…”
Section: Introductionmentioning
confidence: 99%